HADITHS ON CHARACTER EDUCATION: THEMATIC AND CONTEXTUAL ANALYSIS - Muhammad Alif Aulia Rahman; Romlah Abu Bakar Askar; Abdul Ghofur (PT. Jurnal Center Indonesia Publisher, 2025)
Character education is a fundamental aspect of shaping individuals with noble character. In Islam, the hadiths of Prophet Muhammad ﷺ contain numerous character values that serve as life guidelines, such as honesty, trustworthiness, patience, justice, and compassion. This article aims to examine the hadiths related to character education using thematic and contextual approaches. Employing a literature study method, this research collects, categorizes, and analyzes hadiths concerning noble character, then correlates them with the current socio-cultural context. The findings indicate that the values in hadiths are not only relevant for forming Muslim personalities during the Prophet’s time but are also highly applicable in addressing moral challenges in the modern era. The thematic approach aids in systematically summarizing moral messages, while the contextual approach enriches understanding of the original spirit of the teachings. This study recommends integrating hadith-based character values into education as part of an effort to build a generation with strong ethics and integrity.